Girl's Consent in Marriage (Comparative Study Between Imam Shafi'i and Imam Ibn Qayyim al-Jawziyyah) - Arifin Siahaan arifin; Khatibul Umam (Jurnal Sahabat ISNU SU, 2024)
The consent of a prospective bride is one of the most debated issues in Islamic family law. Imam al-Shafi'i argues that the consent of a virgin woman is not a mandatory requirement for the validity of marriage, thereby granting the wali mujbir (guardian with the right of compulsion) the authority to marry her without her explicit consent. In contrast, Ibn Qayyim al-Jawziyyah maintains that the consent of a virgin woman is obligatory as a manifestation of the protection of women's rights and public welfare (maslahah). This study aims to examine the differences in the legal reasoning of Imam al-Shafi'i and Ibn Qayyim al-Jawziyyah regarding a virgin woman's consent to marriage and to evaluate the relevance of their views within the Indonesian legal system. This research employs a normative legal research method using a comparative approach based on library research. Data were analyzed qualitatively by comparing the legal reasoning (istinbāṭ), textual evidence, and legal causes ('illah) adopted by both scholars. The findings reveal that Imam al-Shafi'i relies on the method of mafhūm al-mukhālafah and considers virginity (al-bikr) as the legal cause, thereby recognizing the guardian's right of ijbār. Conversely, Ibn Qayyim al-Jawziyyah adopts the approach of manṭūq al-naṣṣ and regards legal maturity as the determining legal cause, arguing that an adult woman cannot be compelled to marry without her consent. His opinion is considered more consistent with the objectives of Islamic law (maqāṣid al-sharī'ah), the protection of women's rights, and the principle of public welfare. Furthermore, it is more compatible with Indonesian positive law, particularly the Marriage Law and the Compilation of Islamic Law, both of which require the consent of the prospective bride and groom as an essential condition for a valid marriage.